(untitled) (Quinto Sol, 2013)
In this article we specifically analyze free pawns, differentiating within this category, different subgroups according to the form of payment, which correspond to what we know as temporary and permanent laborers and those who were paid per job. We focus on studying how work is regulated and what are the characteristics that it acquires in the late-colonial rural world. The chosen case is Chacarita de los Colegiales, an area specialized in cereal production, especially wheat, destined to supply the city of Buenos Aires.